Penerapan Metode Taguchi dan Grey Relational Analysis pada Optimasi Parameter Mesin EDM Sinking Terhadap Material AISI H13 - Yelse Bella Yulita; Endang Pudji Purwanti; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
EDM sinking is one of the non-conventional machining processes that used to make moulds or dies. In the process, there are several things that affected on the product quality and production cost which are electrode wear rate, surface roughness, final cutting depth and material cutting rate. That four things are influenced by the selection of parameters used during machining process. This research conducted since in the field of industry, optimization becomes an important necessity to improve the quality of products produced. It aims to know how much a parameter contributes to the investigated response and get a combination of parameter settings that are assessed to result in an optimum response simultaneously. This research was conducted on AISI H13 material using Taguchi and Grey Relational Analysis methods. The parameters that researched are current (A), on time (?s), off time (?s), and gap voltage (V). The result of this research is obtained the optimum combination of parameters consisting of the current of 25 ampere, on time of 100 ?s, off time of 10 ?s, and gap voltage of 10 volts with percent contribution of current at 83.90%, on time by 3.46%, off time of 5.48%, and voltage gap of 6.86%.